AN ANALYSIS OF TRANSLATION SHIFT IN ENGLISH-INDONESIAN TRANSLATION OF ERAGON MOVIE - Rini Adriati; Frina Diniarta Nur; Mira Rolianti (STIBA IEC JAKARTA, 2023)
The objectives of this research are to identify the types of translation shifts present in the Eragon movie and to determine their frequency. The data will be collected from the dialogues in the movie. As a basis for this research, there is translation shift theory used, namely the translation shift theory of Catford (1965. In analyzing the data, the author uses a qualitative research methodology with a case study research design. This research identified translation shift occurrence in 599 dialogues and selected 12 samples for detailed analysis and discussion. The findings of the analysis indicated the presence of both Level Shift and Category Shift in the dialogues. The Level Shift is based on grammatical structure, they are Present Perfect Tense, Past Perfect Tense, Past Continuous Tense and Future Tense. The second shift found is Category Shift which consists of four types, they are Structure Shift, Unit Shift, Class Shift and Intra-System Shift. Overall, the results of this research demonstrate the occurrence of both Level Shift and Category Shift in the Eragon movie.